CDK2 inhibition sensitizes anthracycline-induced immunogenic cell death and enhances the efficacy of anti-PD-1 therapy - Chen, Yu; Liu, Wancheng; Cai, Qiaomei; Pan, Chaohu; Yin, Zhenghao; Tang, Yijiao; He, Zhixu; Cheng, Genhong; Shu, Liping (Frontiers in Immunology, 2025)
IntroductionCDK2 (Cyclin-dependent kinase 2) is an oncogenic cyclin-dependent kinase with potent mitogenic and immunosuppressive functions. Despite extensive research on CDK2 inhibitors, the lack of selectivity has made it unclear whether CDK2 inhibition specifically facilitate immunogenic cell death.MethodsWe used CRISPR-Cas9 system to generate Cdk2-/- MCA205 cells. Tumor cells were inoculated subcutaneously into mice while administering MTX (mitoxantrone) or anti-PD-1 antibodies treatment to observe tumor growth curves. Next, immune cell infiltration in tumor microenvironment was detected by immunofluorescence. Furthermore, apoptosis pathway was evaluated by flow cytometry and western blot. The hallmarks of immunogenic cell death were detected by flow cytometry, ELISA or qRT-PCR.ResultsWe found that mice bearing Cdk2-/- cancer cells exhibit slower tumor growth than WT cells after anthracycline analogue MTX treatment, and this phenomenon is dependent on the immune system. Furthermore, our data exhibits that Cdk2-/- cancer cells treated with MTX trigger a more robust immunostimulatory responses than WT cells, including apoptosis stress response, surface calreticulin expression, endoplasmic reticulum stress response, HMGB1 (High Mobility Group Box 1) release, and type-1 interferon response. DiscussionThis study not only suggests that CDK2 inhibition improves the outcome of chemotherapy by enhancing the type-1 interferon response but also investigates the synergistic effects of CDK2 inhibition with MTX or anti-PD-1 antibodies in immunocompetent mice.